Paradygmatyczne konceptualizacje samotności i wspólnotowości w dyskursie monoseologicznym - Domeracki, Piotr (Filozofia Chrześcijańska, 2015)
The author of this paper is concentrated on a controversial and having not only one and satisfactory for different discussing it parts solution problem of the limits of the phenomena of loneliness and communitiveness. It is placed on a ground of the monoseological discourse as being intrinsic to it. The term ‘monoseology’ is derived from two combined ancient Greek words – ‘monosé’, which means ‘loneliness’, and ‘logos’ – translated as ‘science’. Hence monoseology, in its wider meaning, is used to designate all sciences interested in analyzing and conducting systematic research on loneliness; in a narrower sense the term ‘monoseology’ means simply just the philosophy of loneliness. It is quite commonly agreed that loneliness has only got bad sides in itself but communitiveness on the contrary has got only bright ones. Therefore loneliness deserves on clear and firm criticism while communitiveness is assessed in a univocally positive way. This, in turn, translates to an unquestionable preference to ideas, feelings, motives and acts which are of community character and use. On the other hand, loneliness is recognized as a reason of our pain, suffering, fears, sadness and horrible despair. It results that our key ambition, need and aim should be avoiding and preventing each form of loneliness in our private and social life at all costs. But, as it occurs, this causes a lot of further – not only theoretical but unfortunately also practical – problems, which some researchers and ordinary people must face. This kind of unilateral and unambiguous interpretation both loneliness and communitiveness is called in the article “monolectical”. In addition, it is shown in it that ‘monolectics’ of communitiveness or loneliness is insufficient for possibly objective and complete picture of this two. In consequence it is argued that monoseological discourse is able to gain it and to develop itself only by turning to the dialectical method of explaining. The fundamental thesis and belief as well, expressed on the ground of the dialectics of loneliness and communitiveness, is that loneliness and communitiveness are not at all isolated but strongly complementary. A practical conclusion arises from this statement according to which each of us should intertwine in his or her life some periods of communitiveness and then some periods of loneliness.